Serological survey reveals enzootic circulation of St. Louis encephalitis and West Nile viruses in semiarid Monte ecosystem of Argentina - Kevin A. Rucci; Diego L. Arias-Builes; Andrés M. Visintin; Adrián Diaz (Scientific Reports, 2024)
Abstract St. Louis encephalitis virus (SLEV) and West Nile virus (WNV) are arboviruses transmitted by Culex mosquitoes and amplified in avian hosts. The present study aimed to investigate the presence and seasonal circulation of SLEV and WNV in La Rioja province, within the semiarid ecoregion of the Monte, Argentina. Over a two-year period, avian sera were collected and tested for neutralizing antibodies against SLEV and WNV. Our results reveal the enzootic activity of both viruses in this challenging environment. SLEV seroprevalence was 4.5% (35/778), with higher activity in spring (2016) and autumn (2017). WNV seroprevalence was 3.5% (27/778), peaking during the summer 2016–2017. Greater seroprevalence for SLEV in 2016 was detected for the Lark-like Brushrunner (Coryphistera alaudina) and the Short-billed Canastero (Asthenes baeri) and in 2017 for the Black-crested Finch (Lophospingus pusillus) and Lark-like Brushrunner, whereas for WNV greater seroprevalence in 2016 was detected for the Picui Ground Dove (Columbina picui) and in 2017 for the Lark-like Brushrunner and Band-tailed Seedeater (Catamenia analis). Additionally, five avian individuals experienced seroconversion during the sampling period, namely the Lark-like Brushrunner and White-fronted Woodpecker (Melanerpes cactorum) for SLEV, and the Lark-like Brushrunner, Greater Wagtail Tyrant (Stigmatura budytoides) and Many-colored Chaco Finch (Saltatricula multicolor) for WNV. The study highlights the persistence and circulation of these viruses in a semiarid ecosystem, raising questions about overwintering mechanisms and transmission dynamics. This research contributes to understanding arbovirus ecology in diverse environments. Further investigations are needed to assess the specific mechanisms facilitating virus persistence in the Monte ecoregion.